2014
DOI: 10.3389/fpsyg.2014.01215
|View full text |Cite
|
Sign up to set email alerts
|

Chill-inducing music enhances altruism in humans

Abstract: Music is a universal feature of human cultures, and it has both fascinated and troubled many researchers. In this paper we show through the dictator game (DG) that an individual’s listening to preferred “chill-inducing” music may promote altruistic behavior that extends beyond the bounds of kin selection or reciprocal altruism. Participants were 22 undergraduate and postgraduate students who were divided into two groups, the in-group and the out-group, and they acted as dictators. The dictators listened to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 77 publications
0
50
0
1
Order By: Relevance
“…Specifically, Stel et al (2008) demonstrated that participants showed significantly greater readiness to make generous charitable donations if they were emotionally moved beforehand (for a similar line of research see Sze et al, 2012 ). Likewise, in a dictator game paradigm, Fukui and Tyoshima (2014) found enhanced empathy and altruism in participants who experienced music-elicited chills before playing the dictator game. Panksepp and Bernatzky (2002) offered an evolutionary explanation for the nexus between emotional piloerection and social cognition: They theorized that chills (which are readily associated with feeling cold) might have originated as a way to urge the organism to seek close social (and bodily) contact with others and thereby re-establish social bonds (see also Benedek and Kaernbach, 2011 ; Maruskin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Specifically, Stel et al (2008) demonstrated that participants showed significantly greater readiness to make generous charitable donations if they were emotionally moved beforehand (for a similar line of research see Sze et al, 2012 ). Likewise, in a dictator game paradigm, Fukui and Tyoshima (2014) found enhanced empathy and altruism in participants who experienced music-elicited chills before playing the dictator game. Panksepp and Bernatzky (2002) offered an evolutionary explanation for the nexus between emotional piloerection and social cognition: They theorized that chills (which are readily associated with feeling cold) might have originated as a way to urge the organism to seek close social (and bodily) contact with others and thereby re-establish social bonds (see also Benedek and Kaernbach, 2011 ; Maruskin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 93%
“…Emotional intensity is further amplified by the use of musical scores and the depiction of singing characters. Music and singing have often been shown to be capable of eliciting peak emotional responses including piloerection/chills and tears on their own ( Panksepp, 1995 ; Blood and Zatorre, 2001 ; Scherer and Zentner, 2001 ; Scherer et al, 2002 ; Rickard, 2004 ; Grewe et al, 2007 , 2009 ; Guhn et al, 2007 ; Salimpoor et al, 2009 , 2011 ; Fukui and Tyoshima, 2014 ). Finally, tears-eliciting clips used significantly more point-of-view shots which facilitate perspective taking and thereby empathic responses on the side of the film viewer.…”
Section: Discussionmentioning
confidence: 99%
“…The strong and unusual empathy mentioned by our subjects leads us to propose that one of the fundamental human conflicts which chill-eliciting scenes might help resolve and overcome is the fact that humans survive by sharing goals but can never access to these goals directly (nobody will ever have directly access to your thoughts and conversely you will never have directly access to somebody else's thoughts). Another fundamental conflict that chill-eliciting stimuli might help overcome is the altruistic nature of human beings as opposed to the high degree of egoism presented by contemporary cultures (see for example Keltner, 2009 ; Fukui and Toyoshima, 2014 or Piff et al, 2015 ). The narratological results seem to suggest that they do so by displaying situations where empathy is necessary to reduce the narrative tension to a minimum.…”
Section: Discussionmentioning
confidence: 99%
“…However, other researchers pointed out that being moved, being a pro-social emotion, may stimulate a broader range of altruistic behaviours like helping, consolidating, and being generous (e.g. Fukui & Toyoshima, 2014;Stel, Van Baaren, & Vonk, 2008). It is also possible that being moved creates an even more general motivational state, which facilitates the pursuit of any current goal, independent of its content.…”
Section: Discussionmentioning
confidence: 99%